Ligand tunnels in T. brucei and human CYP51: Insights for parasite-specific drug design - Yu, Xiaofeng; Nandekar, Prajwal; Mustafa, Ghulam; Cojocaru, Vlad; Lepesheva, Galina I.; Wade, Rebecca C. (Biochimica et biophysica acta, 2015)
Background - Cytochrome P450 sterol 14α-demethylase (CYP51) is an essential enzyme for sterol biosynthesis and a target for anti-parasitic drug design. However, the design of parasite-specific drugs that inhibit parasitic CYP51 without severe side effects remains challenging. The active site of CYP51 is situated in the interior of the protein. Here, we characterize the potential ligand egress routes and mechanisms in Trypanosoma brucei and human CYP51 enzymes. - Methods - We performed Random Acceleration Molecular Dynamics simulations of the egress of four different ligands from the active site of models of soluble and membrane-bound T. brucei CYP51 and of soluble human CYP51. - Results - In the simulations, tunnel 2f, which leads to the membrane, was found to be the predominant ligand egress tunnel for all the ligands studied. Tunnels S, 1 and W, which lead to the cytosol, were also used in T. brucei CYP51, whereas tunnel 1 was the only other tunnel used significantly in human CYP51. The common tunnels found previously in other CYPs were barely used. The ligand egress times were shorter for human than T. brucei CYP51, suggesting lower barriers to ligand passage. Two gating residues, F105 and M460, in T. brucei CYP51 that modulate the opening of tunnels 2f and S were identified. - Conclusions - Although the main egress tunnel was the same, differences in the tunnel-lining residues, ligand passage and tunnel usage were found between T. brucei and human CYP51s. - General Significance - The results provide a basis for the design of selective anti-parasitic agents targeting the ligand tunnels.